Bull Dog Monster Calf With Achondroplasia And Ascites In A Cross Bred Cow - Rani, R. Uma; Muruganandan , B. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Various kinds of foetal anomalies and monstrosities cause dystocia in cows (Sloss and Dufty, 1980, Arthur et al. 1996 and Sathiamoorthy et al., 2011). Occurrence of “Bull dog” monstrosity is a very rare condition (Noakes et al., 2001). The present report records a case of dystocia due to bull dog monster calf with achondroplasia and ascites in a Jersey cross bred cow.